2007
DOI: 10.1111/j.1462-5822.2006.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Budding of Marburgvirus is associated with filopodia

Abstract: SummaryViruses exploit the cytoskeleton of host cells to transport their components and spread to neighbouring cells. Here we show that the actin cytoskeleton is involved in the release of Marburgvirus (MARV) particles. We found that peripherally located nucleocapsids and envelope precursors of MARV are located either at the tip or at the side of filopodial actin bundles. Importantly, viral budding was almost exclusively detected at filopodia. Inhibiting actin polymerization in MARV-infected cells significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 95 publications
(131 reference statements)
8
104
0
Order By: Relevance
“…Viral infection also caused extensive cytoskeletal changes which may have some bearing on normal synaptogenesis in vivo. In addition, actin cytoskeletal hijacking may be a common viral invasion strategy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Viral infection also caused extensive cytoskeletal changes which may have some bearing on normal synaptogenesis in vivo. In addition, actin cytoskeletal hijacking may be a common viral invasion strategy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Later in the replication cycle, NCs are detected in the cytosol, at the plasma membrane, and in filopodia, the preferred sites of MARV budding (12,13). The glycoprotein GP reaches the plasma membrane via vesicular secretory membrane traffic and is recruited to sites where viral protein VP40 accumulates (14,15).…”
mentioning
confidence: 99%
“…Interestingly, marburgvirus NP also contains the late domain motif and interacts with Tsg101 [82], suggesting that NP may share transport pathways with VP40. It was indeed demonstrated that both VP40 and nucleocapsid were associated with cytoskeletal proteins such as actins in cytoplasmic transport [83][84][85][86]. Since VP40 is also detected in inclusion bodies along with NP and VP35 [68], it is of interest to clarify whether the nucleocapsid is trafficked to the assembly site alone or with VP40.…”
Section: Assembly/egressmentioning
confidence: 99%
“…It is assumed that majority of marburgvirus particles are released from the tips or sides of cellular filopodia [83]. It has been shown that actindependent molecular motor protein Myo10, which mediates intrafilopodial movement of proteins, is important for VP40-mediated vesicle release [83]. Similarly, IQGAP1, which is involved in cytoskeletal remodeling during cell migration and the formation of filopodia, interacts with ebolavirus VP40 and facilitates the release of virus-like particles [88].…”
Section: Assembly/egressmentioning
confidence: 99%
See 1 more Smart Citation